1993
DOI: 10.1093/eurheartj/14.12.1661
|View full text |Cite
|
Sign up to set email alerts
|

PTCA in elderly patients: acute results and long-term follow-up

Abstract: Acute results and long-term follow-up of percutaneous transluminal coronary angioplasty (PTCA) in 125 patients aged 75 to 90 years (79 men; 46 female; mean age 78 +/- 3 years), with mainly unstable angina (102 patients) are reported. Successful PTCA was achieved in 96 out of 108 patients (89%); occlusions could be reopened in eight out of 17 patients (47%). Thirty-eight procedures were multiple vessel or multiple lesion PTCA, so that the lesion-related success rate of PTCA was higher (91%). Major complications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Direct coronary angioplasty performed in elderly patients (>75 years) was reported as a high-risk procedure due to the greater index of complications. The in-hospital mortality reported is greater in patients in this age group (0.8 to 8.5%) as compared with that in younger patients (0 to 1.8%) [11][12][13][14][16][17][18][19] . Hartzler et al 20 reported a 2.6 relative risk for mortality after direct coronary angioplasty in patients > 70 years, and, in this study, we found the same 2.6 relative risk using a cutoff for age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…Direct coronary angioplasty performed in elderly patients (>75 years) was reported as a high-risk procedure due to the greater index of complications. The in-hospital mortality reported is greater in patients in this age group (0.8 to 8.5%) as compared with that in younger patients (0 to 1.8%) [11][12][13][14][16][17][18][19] . Hartzler et al 20 reported a 2.6 relative risk for mortality after direct coronary angioplasty in patients > 70 years, and, in this study, we found the same 2.6 relative risk using a cutoff for age of 65 years.…”
Section: Discussionmentioning
confidence: 99%
“…While octogenarian patients have been followed for up to 7 years after coronary angioplasty [7][8][9][10] , little is known about the effect of PTCA on patients' symptoms and its relative costs as compared with younger patients. We report the results of a prospective study on quality of life and costs of PTCA among patients above 80 years and a younger control group.…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous coronary intervention (PCI) is increasingly used in elderly patients with coronary artery disease, as improved outcomes compared with medical treatment support the use of invasive procedures in these patients. [14][15][16][17][18] However, expansion of the indications for PCI, including the elderly patient, has resulted in increasing patient volumes in many catheter labs. Managing this large number of patients, often with no increasing resources, is a challenge for many centers.…”
Section: Discussionmentioning
confidence: 99%